2020
DOI: 10.1177/1747021820969037
|View full text |Cite
|
Sign up to set email alerts
|

The attentional boost effect with semantic information detection tasks

Abstract: The attentional boost effect (ABE) is a phenomenon in which in some dual tasks, increased attention to target detection causes an increase in memory performance related to items paired with the target. However, in previous studies concerning the ABE, the detection task objects usually reflected perceptual information. Whether the ABE could be observed if the task involves detecting semantic information is unclear. To answer this question, the present study adopted the classic dual-task paradigm of the ABE. Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…A between-experiment comparison showed that, in the category search task, the ABE was comparable in magnitude between Experiments 1 and 2, t (94) = 0.95, p = .347, Cohen’s d = 0.19, despite the target being infrequent in Experiment 1 and common in Experiment 2. This finding aligns with previous ABE studies, indicating the ABE’s insensitivity to target and stimulus frequencies (e.g., comparable results between a target-to-distractor ratio of 1:1 and 1:6 in Makovski et al, 2011; Swallow & Jiang, 2012; Zheng et al, 2021), although these studies did not involve categorical stimuli like letters and digits.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…A between-experiment comparison showed that, in the category search task, the ABE was comparable in magnitude between Experiments 1 and 2, t (94) = 0.95, p = .347, Cohen’s d = 0.19, despite the target being infrequent in Experiment 1 and common in Experiment 2. This finding aligns with previous ABE studies, indicating the ABE’s insensitivity to target and stimulus frequencies (e.g., comparable results between a target-to-distractor ratio of 1:1 and 1:6 in Makovski et al, 2011; Swallow & Jiang, 2012; Zheng et al, 2021), although these studies did not involve categorical stimuli like letters and digits.…”
Section: Methodssupporting
confidence: 91%
“…Unfortunately, the availability of "face norms" (i.e., the mental representation of an average male or female face) enabled participants to perform the gender task by matching each face against a single face norm, bypassing the need to search for multiple possible targets. Another study asked participants to respond to odd digits among even digits (Zheng et al, 2021), necessitating category search. Memory accuracy in that study, however, was at chance levels, raising doubts about the robustness of the ABE under such conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming a cascading sequence of processing stages, from sensory processing, to perceptual identification of the target, to the subsequent response, the attentional boost effect has a relatively “late” locus. This finding may explain why increasing attentional demands at earlier stages, such as through a manipulation of target-distractor similarity in the RSVP task, did little to modulate the attentional boost effect (Swallow & Jiang, 2010, 2014b; Zheng et al, 2021; the current study). This explanation is consistent with Swallow and Jiang (2014b), who showed that the attentional boost applies only to stimuli that are ultimately categorized as the task target.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, finding a target, rather than responding to it, may be critical for forming associative learning between the target and the distractor layout. Unlike contextual cuing, however, the attentional boost effect does not depend on repeated pairing of the RSVP task and the background images (Mulligan et al, 2016; Sisk & Lee, 2021; Turker & Swallow, 2019; Zheng et al, 2021). As a temporal orienting effect (Swallow & Jiang, 2013), it may be governed by different mechanisms than contextual cuing.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation